Thermal stability and decomposition mechanism of HFO‐1336mzz(Z) as an environmental friendly working fluid: Experimental and theoretical study. (15th May 2019) - Huo, Erguang; Liu, Chao; Xin, Liyong; Li, Xiaoxiao; Xu, Xiaoxiao; Li, Qibin; Wang, Shukun; Dang, Chaobin
Summary: HFO‐1336mzz(Z) is a promising working fluid used in high‐temperature heat pump and organic Rankine cycle (ORC) system because of its environmental friendly features and good thermal performance. In this work, a test system is designed to assess the thermal stability of HFO‐1336mzz(Z). The fluoride ion concentration is used as an indicator of HFO‐1336mzz(Z) dissociation. The experimental results show that the pressure has a great effect on the dissociation of HFO‐1336mzz(Z) and the dissociation temperatures of HFO‐1336mzz(Z) at 2.1, 3.1, and 4.0 MPa for 24 hours are 310°C to 330°C, 290°C to 310°C, and 270°C to 290°C, respectively. The decomposition products of HFO‐1336mzz(Z) are measured by a Fourier transform infrared spectrometer (FTIR); the main decomposition products are HF, CF4, CHF3, C2F4, C2 F6, C2 HF5, and C3 F8 . Finally, density functional theory (DFT) method is used to study the decomposition mechanism of HFO‐1336mzz(Z). The main initial decomposition reaction is the fracture of CC bond into C–C bond, and then the CF3 group is separated from HFO‐1336mzz(Z) molecule to produce CF3 radical. H, F‐abstraction, and combination reactions are important in the consequent reactions to generate the main decomposition products. Abstract : The thermal stability of HFO‐1336mzz(Z) at different conditions is investigated. The decomposition products of HFO‐1336mzz(Z) are measured. The decomposition mechanism of HFO‐1336mzz(Z) is illustrated.